Effects of an Acute Bout of Physical Exercise on Reward Functioning in Healthy Adults - Wardle, Margaret C. (Physiol Behav, 2018)
Exercise has been proposed as a treatment for several psychiatric disorders. Exercise may act in part through beneficial effects on reward functioning, as it alters neurotransmitter levels in reward-related circuits. However, there has been little investigation of the effect of exercise on reward functions in humans. We hypothesized an acute bout of exercise would increase motivation for and pleasurable responses to rewards in healthy humans. In addition, we examined possible moderators of exercise’s effects, including demographics, fitness and previous exercise experience. Thirty-five participants completed exercise and sedentary control sessions in randomized, counterbalanced order on separate days. Immediately after each activity, participants completed measures of motivation for and pleasurable responses to rewards, consisting of willingness to exert effort for monetary rewards and subjective responses to emotional pictures. Exercise did not increase motivation or pleasurable responses on average. However, individuals who had been running for more years showed increases in motivation for rewards after exercise, while individuals with less years running showed decreases. Further, individuals with higher resting heart rate variability reported lower arousal in response to all emotional pictures after exercise, while individuals with low heart rate variability reported increased arousal in response to all emotional pictures after exercise. General fitness did not have similar moderating effects. In conclusion, acute exercise improved reward functioning only in individuals accustomed to that type of exercise. This suggests a possible conditioned effect of exercise on reward functioning. Previous experience with the exercise used should be examined as a possible moderator in exercise treatment trials.